A Novel 2D Metal Flow Model for Hot Rolling of Aluminum Alloy Thick Plate - Pujun Hao; Jingna Liu; Chihuan Yao (Advances in Materials Science and Engineering)
Considering the serious inhomogeneous distribution of plastic deformation in the rolling process of thick plate, a novel 2D metal flow model is proposed with a quadratic distribution of flow velocity in the thickness direction instead of an equal value used in traditional metal flow models. According to the energy method, this model is solved. Through comparing with the experimental data of rolling force, the accuracy of this model is validated. Then, it is found that with the increase in roll speed, the neutral point moves towards the exit of the deformation zone. However, compared with other models of metal flow in rolling process, the neutral point is distributed much closer to the entrance of the deformation zone. That is because with the quadratic distribution of flow velocity in thickness direction, flow velocity of metal at the surface increases faster than average flow velocity of metal, so that the neutral point appears earlier.